Palladium(ii) complexes with a phosphino-oxime ligand: synthesis, structure and applications to the catalytic rearrangement and dehydration of aldoximes1. Issue 7 (22nd July 2015) - Menéndez-Rodríguez, Lucía; Tomás-Mendivil, Eder; Francos, Javier; Nájera, Carmen; Crochet, Pascale; Cadierno, Victorio
<x xml:space="preserve">Abstract</x> The catalytic rearrangement and dehydration of aldoximes with phosphino-oxime-palladium complexes is described.